Adoption of a biologically-enhanced agricultural management (BEAM) approach in agroecosystems for regenerating soil fertility, improving farm profitability and achieving productive utilization of atmospheric CO2 - David C. Johnson; Hui-Chun Su Johnson (PeerJ)
Background A 4-year field study, on the adoption of a Biologically-Enhanced Agricultural Management (BEAM) protocol, in a cotton/cover-crop rotation in Turkey, was designed to observe “change-over-time” of soil organic carbon (SOC%) and total soil nitrogen (TSN%) at three soil profile depths (0–15 cm, 15–30 cm and 30–45 cm) while tracking farm productivity and profitability. Methods BEAM systems employ regenerative practices: (a) no-till, (b) no, or reduced synthetic nutrient amendments, (c) continuous roots in the ground (commodity/cover), accompanied with an injection (in-furrow at planting) of an extract of beneficial microbes, from a Johnson-Su bioreactor. Three field nitrogen treatments: (1) BEAM+100% N (203 kg N ha−1); (2) BEAM+15% N (30.53 kg N ha−1); and (3) BEAM-0% N (No N applied), were implemented, on a 5.22-hectare plot, to assess the influence of BEAM protocols and nitrogen amendments, on SOC%, TSN%, cotton production, and profitability. Results The SOC%, in the 0–15 cm soil profile demonstrated a significant increase from 0.39% SOC to 1.83% SOC, for a total increase of 1.44%, over the 4-year study period, (y = 0.3136x + 0.1206; r2 = 0.96; F(1,2) = 45.1616, p = 0.02143); The 15–30 cm soil profile demonstrated a non-significant loss of −0.23% SOC (y = −0.3161x + 0.156; r2 = 0.3183; F(1,2) = 0.9339, p = 0.4358), and the 30–45 cm soil profile exhibited a significant increase of 0.28% SOC; (y = 0.0477x + 0.4743; r2 = 0.9363; F(1,2) = 29.4005, p = 0.03237). Annual SOC cumulative increases of ~6.59 metric tons (t) carbon (C) ha−1yr−1, were observed, from 2019 to 2023, in the top 45 cm of the soil profile along with annual TSN increases of ~0.68 t N ha−1yr−1 in all three treatments. Cover-crop aboveground biomass increased annually in 2021, 2022 and 2023 from ~400 g, to ~692 g, to ~925 g dry biomass m−2yr−1 providing annual agroecosystem surface carbon accumulation of ~1.78 t C, ~3.08 t C and ~4.11 t C ha−1. Earthworm populations increased from zero earthworms m−2 in 2019 to ~100 earthworms m−2 in 2023. BEAM protocols also promoted: (a) farm input reductions of: 100% for herbicide, 56% for insecticide, 61% for diesel fuel, 85% for synthetic nitrogen fertilizer, and 100% for phosphorus fertilizer applications, reducing farm input costs ~$470 ha−1yr−1. Adoption of a BEAM regenerative agricultural management system, increased: (a) SOC (~6.59 t C ha−1yr−1); (b) C in the annual growth of cover-crop biomass (~4.12 t of C ha−1yr−1); (c) carbon in residual surface cover-crop plant residues from previous annual cover crops (~0.82 t C ha−1yr−1); and (d) C exported in cotton lint (~0.77 t C ha−1yr−1). Total C avoidance included: (a) reductions in fertilizer, pesticides and diesel inputs (~0.33 t C ha−1yr−1); and (b) reduction of C respiration from adoption of zero-till (~0.64 t C ha−1yr−1). Adoption of BEAM management, in this cotton/cover-crop agroecosystem, provided productive utilization, or avoidance of ~13.27 t of atmospheric C ha−1yr−1.